Model Inovatif Pendidikan Agama Islam untuk Era Society 5.0: Sintesis Konstruktivisme, Heutagogi, dan TPACK: Tinjauan Pustaka Sistematis dan Analisis Isi - Muhammad Hanan Putra Ardani; Muhammad Arifin; Eko Ngabdul Shodikin (KAMALIYAH : Jurnal Pendidikan Agama Islam, 2025)
The Society 5.0 requires education that is human-centered while meaningfully utilizing digital technology. Islamic Religious Education (IRE) in many institutions still faces challenges such as one-way instruction, varying levels of teachers’ digital literacy, and curricula not yet integrated with contemporary needs. This study aims to formulate an innovative IRE model relevant to Society 5.0 through a systematic literature review and content analysis to map key themes, gaps, and implications for reform. The synthesis produces an integrated design based on three theoretical foundations: social constructivism, heutagogy, and technological pedagogical content knowledge (TPACK). The model is embodied in three pillars: digital transformation of learning, value- and digital-manners-based learning, and project-based learning that links scriptural principles with real-world issues.  Evaluation  is  conducted  authentically  through  layered  assessments,  including  cognitive  tests, collaboration  records,  platform  analytics,  and  learners’  reflective  journals.  The  integration  of  theory, technology, and character enhances the relevance and effectiveness of learning, provided that teacher capacity, ethical  data  governance,  and  minimum  infrastructure  are  strengthened.  This  model  offers  a  measurable roadmap  for  reorienting  Islamic  Religious  Education  toward  contextual,  humanistic,  and  transformative learning